SUITABILITY STUDY OF ANO ALIAKMONAS RIVER BEDS FOR THE DEVELOPMENT OF RAFTING - Παυλίδης Τ.; Δημητριάδης Ι.; Γκαϊτατζής Δ.; Τσιώρας Π. (Bulletin of the Geological Society of Greece, 2018)
The river and torrents sports (rafting, canoe kayak) have spread in Greece during the last years. These sports, with an increasing number of friends, are centered at Evinos and Aoos rivers, due to their hydrologie and géomorphologie suitability. The impressive routes, the fascination of these sports as well as their organization at different seasons (winter-spring season) create an increasing demand of new impressive routes, which will also fulfill the appropriate géomorphologie and hydrologic prerequisites. The very exciting sport of rafting can act as an important factor for the development of alternative forms of inner tourism, in the context of supporting the less developed mountain areas in Greece. This paper is investigating the suitability of the proposed routes in terms of geometry and morphology (width, length and inclinations of the river bed etc) as well as hydrology (sufficient water load movement for a long time which will reinsure the desired river bed, rainfall intensity etc). All of the above are investigated in the context of achieving the high levels of satisfaction from the rafting experience and the connection of the suggested routes with their starting and finishing points.